2012
DOI: 10.1007/s11033-012-2096-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of JAK2 and STAT3 variants to the genetic susceptibility of recurrent miscarriage among Bahraini and Tunisian Arabs

Abstract: We investigated the contribution of JAK2 rs2203724 and STAT3 rs1053023 and rs1053004 to the susceptibility of idiopathic recurrent miscarriage (IRM) in Bahraini (246 cases and 279 controls) and Tunisian (235 cases and 235 controls) Arabs. The distribution of JAK2 rs2203724 and STAT3 rs1053023 genotypes were in Hardy-Weinberg equilibrium (HWE) in both communities, while mild deviation from HWE was noted for rs1053004 in Tunisians but not Bahraini. JAK2 rs2203724 was not associated with IRM in either community, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…These findings were consistent with the data conducted in the recent Chinese cohort (T allele: 65.63% and C allele: 34.37%) (Xie et al, 2013), suggesting that the SNP has homogeneity in the allele distribution among East-Asian (Thai and Chinese) populations. Interestingly, in contrast to our report, the frequency of C allele was higher than T allele in Tunisian Arabs (Middle East) (Messaoudi et al, 2013a;2013b). SNP rs1053004, localized on 3'-UTR of STAT3, regulates expression of STAT3 protein by altering mRNA degradation and decreased STAT3 activity (Foshay and Gallicano, 2009;Xie et al, 2013).…”
Section: Discussioncontrasting
confidence: 95%
“…These findings were consistent with the data conducted in the recent Chinese cohort (T allele: 65.63% and C allele: 34.37%) (Xie et al, 2013), suggesting that the SNP has homogeneity in the allele distribution among East-Asian (Thai and Chinese) populations. Interestingly, in contrast to our report, the frequency of C allele was higher than T allele in Tunisian Arabs (Middle East) (Messaoudi et al, 2013a;2013b). SNP rs1053004, localized on 3'-UTR of STAT3, regulates expression of STAT3 protein by altering mRNA degradation and decreased STAT3 activity (Foshay and Gallicano, 2009;Xie et al, 2013).…”
Section: Discussioncontrasting
confidence: 95%
“…43 Besides, Messaoudi et al, reported that the G allele in rs1053023 polymorphism is associated with recurrent miscarriages in Bahraini and Tunisian Arab populations. 44,45 This result was not surprising, as previous studies revealed higher levels of p-STAT3, IL17, and IL17R in patients with unexplained recurrent spontaneous abortions. 46,47 In another study evaluating the association between these two polymorphisms in STAT3 and the risk of developing noise-induced hearing loss (NIHL), it was demonstrated that the G allele in both variants was linked with NIHL risk.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, the IL-1 family is well-known to be involved in inflammation; specifically, the role of IL-1β in relation to the development of inflammatory diseases is well established [ 34 ]. Moreover, studies of the STAT3 rs1053004, IL-6 rs1800796, and TNF-α rs1800629 polymorphisms suggested their significant association with recurrent miscarriage as well as abnormal inflammation responses [ 6 , 35 , 36 , 37 , 38 , 39 ]. Specifically, the IL-6 rs1800796 G and TNF-α rs1800629 A alleles have significant associations with an increased risk of pregnancy complications [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%